Interpersonal Violence, Racial Discrimination, and Mental Health Symptoms Among Adolescents of Color in the Juvenile-Justice System - Jouriles, Ernest N. (Journal of interpersonal violence, 2024)
The current study examined how interpersonal racial discrimination experiences operate together with other forms of interpersonal violence to contribute to mental health symptoms among justice-involved adolescents of color. Participants were 118 justice-involved adolescents of color aged 14 to 17 (M = 15.77, SD = 1.08; 52.5% male; 77.1% Black/African American) and their mothers. At baseline, adolescents reported on experiences of interpersonal racial discrimination, harsh parenting, teen dating violence, and exposure to interparental physical intimate partner violence. At baseline and the 3-month follow-up assessment, adolescents reported on trauma symptoms, and adolescents and their mothers reported on the adolescents’ externalizing and internalizing symptoms. Multivariate multilevel modeling results indicated that interpersonal racial discrimination experiences contributed additively to adolescent mental health symptoms at both the baseline and 3-month follow-up assessments, after accounting for exposure to other forms of interpersonal violence. The current findings highlight the importance of considering adolescents’ experiences of interpersonal racial discrimination, together with other forms of interpersonal violence, in work focused on understanding the mental health symptoms of justice-involved adolescents of color.